2017
DOI: 10.3390/ijms18051088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Promotes Salinomycin-Induced Apoptosis via Reactive Oxygen Species-Mediated PI3K/AKT/mTOR and ERK/p38 MAPK-Dependent Signaling in Human Prostate Cancer Cells

Abstract: Recently, the interplay between autophagy and apoptosis has become an important factor in chemotherapy for cancer treatment. Inhibition of autophagy may be an effective strategy to improve the treatment of chemo-resistant cancer by consistent exposure to chemotherapeutic drugs. However, no reports have clearly elucidated the underlying mechanisms. Therefore, in this study, we assessed whether salinomycin, a promising anticancer drug, induces apoptosis and elucidated potential antitumor mechanisms in chemo-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 32 publications
(39 reference statements)
8
110
0
Order By: Relevance
“…Also, Salinomycin, a natural compound isolated from Streptomyces albus, was shown to induce p38 MAPK-mediated downregulation of the AKT/mTOR pathway, protective autophagy, and apoptosis in human prostate cancer cells [44]. Inhibition of autophagy with 3-MA enhanced Salinomycine-induced apoptosis and pretreatment with the p38 inhibitor SB 203,580 decreased salinomycin-induced autophagy [44]. Here we showed that OMEO activated both autophagy and apoptosis, with autophagy occurring first.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Also, Salinomycin, a natural compound isolated from Streptomyces albus, was shown to induce p38 MAPK-mediated downregulation of the AKT/mTOR pathway, protective autophagy, and apoptosis in human prostate cancer cells [44]. Inhibition of autophagy with 3-MA enhanced Salinomycine-induced apoptosis and pretreatment with the p38 inhibitor SB 203,580 decreased salinomycin-induced autophagy [44]. Here we showed that OMEO activated both autophagy and apoptosis, with autophagy occurring first.…”
Section: Discussionmentioning
confidence: 65%
“…Pharmacological inhibition of autophagy by 3-MA increased Resveratrol-induced cell death, while inhibition of p38 MAPK by SB 203,580 exerted the opposite effect [39]. Also, Salinomycin, a natural compound isolated from Streptomyces albus, was shown to induce p38 MAPK-mediated downregulation of the AKT/mTOR pathway, protective autophagy, and apoptosis in human prostate cancer cells [44]. Inhibition of autophagy with 3-MA enhanced Salinomycine-induced apoptosis and pretreatment with the p38 inhibitor SB 203,580 decreased salinomycin-induced autophagy [44].…”
Section: Discussionmentioning
confidence: 98%
“…A study on HT1080 human fibrosarcoma cells showed that Silibinin induces autophagy through the activation of ROS-p38 [12]. Kim et al [38] also confirmed that Salinomycin induced autophagy through regulation of the ROS-mediated p38-MAPK signaling pathway in human prostate cancer cells. Ahn et al [9] reported that Shikonin could activate the p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 91%
“…While several publications have reported that salinomycin suppresses autophagy, 24,25 others have claimed that it induces autophagy. 22,25,26 This controversy may be due to technical differences in the methods used to detect autophagy.…”
Section: Identification Of Compounds Synergizing With Autophagy Inhmentioning
confidence: 99%